Evaluation of crown-root angulation of lateral incisors adjacent to palatally impacted canines. - Kanavakis, Georgios.; Curran, Karen M.; Wiseman, Kevin C.; Barone, Nicholas P.; Finkelman, Matthew D.; Srinivasan, Sreedevi.; Lee, Moonyoung B.; Trotman, Caroll-Ann. (2016)
Background: The objective of this study is to explore differences in crown-to-root angulation between lateral incisors adjacent to palatally impacted canines (PICs) and lateral incisors adjacent to normally erupted canines (NECs).; Keywords: Palatally impacted canines, Panoramic images, Lateral incisor morphology, Crown-to-root angulation.; Springer Open.